2020
DOI: 10.1055/s-0040-1721463
|View full text |Cite
|
Sign up to set email alerts
|

Women's Experiences of Diagnosis and Treatment of Early Menopause and Premature Ovarian Insufficiency: A Qualitative Study

Abstract: Early menopause (EM) and premature ovarian insufficiency (POI) affect an estimated 10% of women and can precipitate a wide range of physiological and personal impacts. Receiving a diagnosis of EM/POI and navigating treatment can be complex experiences for women; however, qualitative research exploring these aspects of the condition is limited. Our study aimed to increase understanding of women's lived experiences of EM/POI encompassing its medical, social, and emotional dimensions. We conducted narrative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Analysis of interviews with 30 women aged 28 to 51 (diagnosis age 25-44 years) with spontaneous (n ¼ 11) or iatrogenic (n ¼ 19) EM/POI identified low EM/POI awareness; dissatisfaction with diagnosis process; multiple disabling symptoms; uncertainty about EM/POI health impacts and treatments; variable effectiveness of therapies; significant personal/social impacts; appreciation for knowledgeable and empathetic HPs; uneven access to care; and lack of online information. 6,23 Analysis of interviews with 16 HPs (aged 35 years to late 60s, with 7-35 years of experience caring for women with EM/POI) identified the need for: faster/more empathetic diagnosis; holistic care; multiple treatment options; multidisciplinary care; tailored, credible resources; improved care access for regional women; and shared decision-making.…”
Section: Qualitative Interviews With Women and Hps To Explore Experiences Of And Perspectives On Em/poimentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of interviews with 30 women aged 28 to 51 (diagnosis age 25-44 years) with spontaneous (n ¼ 11) or iatrogenic (n ¼ 19) EM/POI identified low EM/POI awareness; dissatisfaction with diagnosis process; multiple disabling symptoms; uncertainty about EM/POI health impacts and treatments; variable effectiveness of therapies; significant personal/social impacts; appreciation for knowledgeable and empathetic HPs; uneven access to care; and lack of online information. 6,23 Analysis of interviews with 16 HPs (aged 35 years to late 60s, with 7-35 years of experience caring for women with EM/POI) identified the need for: faster/more empathetic diagnosis; holistic care; multiple treatment options; multidisciplinary care; tailored, credible resources; improved care access for regional women; and shared decision-making.…”
Section: Qualitative Interviews With Women and Hps To Explore Experiences Of And Perspectives On Em/poimentioning
confidence: 99%
“…We have previously reported in detail on the mixed methods iterative research across Phases 1 and 2. 6,[20][21][22][23] This article aims to describe and summarize the overall process of co-design and, for the first time, report on the development (Phase 3) and evaluation (Phase 4) of the digital resource as well as dissemination and implementation (Phase 5).…”
mentioning
confidence: 99%
“…4,5 The common triad of diagnosis includes hypergonadotropic hypogonadism, hypoestrogenism, 6 and secondary amenorrhea. 7 However, the term “POI” is not exactly the same as menopause; some women with POI still have the ability to ovulate 8 and in 5%–10% of cases they may become pregnant naturally. 9 The age of onset of the illness varies widely, even from birth to 11 years.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian research team aimed to increase understanding of women's lived experiences of this by interviewing 30 women aged between 28 and 51 years. 2 They found that women have to come to terms with its often harsh consequencesfertility loss, menopausal symptoms, longterm health effects, impacts on sexuality, and often a sense of no longer fitting with socially and culturally-shaped ideas on 'youth' and attractiveness. The authors suggest clinicians can improve their care of these women by making use of new digital resources including online diagnostic and management algorithms, acknowledging potential distress, and recognising that the impact of the condition can extend to women's social identities, relationships, and work.…”
mentioning
confidence: 99%